PENINGKATAN DAYA SAING UMKM MELALUI DIGITALISASI PEMASARAN PRODUK PADA MEDIA SOSIAL TIKTOK - Mulyani, Mulyani; Sari, Riska Nadya; Selpiana, Selpiana; Oktavia, Tarisa; Rahmawati, Tika (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2026)
ABSTRACT The development of digital technology encourages micro, small, and medium enterprises (MSMEs) to adopt social media–based marketing strategies in order to enhance business visibility and competitiveness. However, many traditional MSMEs still face limitations in digital literacy and remain dependent on conventional marketing practices, as experienced by UD Sumber Genteng. This community service activity focuses on strengthening the partner’s digital capacity through mentoring in the use of the TikTok platform as a product promotion medium. The stages of the activity include identifying the partner’s needs, mentoring in the establishment of a digital identity, training in content planning and production that highlights the roof tile manufacturing process, and an initial evaluation of the partner’s readiness to manage digital marketing independently. The results indicate an improvement in the partner’s understanding of the importance of digital identity, enhanced ability to develop more targeted and authentic promotional content, and initial readiness to implement social media–based marketing strategies in a sustainable manner. This activity concludes that optimizing TikTok as a marketing medium has the potential to expand market reach and improve the competitiveness of traditional MSMEs, provided it is supported by continuous mentoring and consistency in digital content management. ABSTRAK Perkembangan teknologi digital mendorong pelaku usaha mikro, kecil, dan menengah (UMKM) untuk mengadopsi strategi pemasaran berbasis media sosial guna meningkatkan visibilitas dan daya saing usaha. Namun, sebagian UMKM tradisional masih menghadapi keterbatasan literasi digital dan ketergantungan pada pola pemasaran konvensional, sebagaimana dialami oleh UD Sumber Genteng. Kegiatan pengabdian kepada masyarakat ini berfokus pada peningkatan kapasitas digital mitra melalui pendampingan pemanfaatan platform TikTok sebagai sarana promosi produk. Tahapan kegiatan meliputi identifikasi kebutuhan mitra, pendampingan pembentukan identitas digital, pelatihan perencanaan dan produksi konten yang menonjolkan proses pembuatan genteng, serta evaluasi awal kesiapan mitra dalam mengelola pemasaran digital secara mandiri. Hasil kegiatan menunjukkan adanya peningkatan pemahaman mitra terhadap pentingnya identitas digital, kemampuan menyusun konten promosi yang lebih terarah dan autentik, serta kesiapan awal dalam menerapkan pemasaran berbasis media sosial secara berkelanjutan. Kegiatan ini menyimpulkan bahwa optimalisasi TikTok sebagai media pemasaran berpotensi memperluas jangkauan pasar dan meningkatkan daya saing UMKM tradisional apabila didukung oleh pendampingan berkelanjutan serta konsistensi dalam pengelolaan konten digital.